2020
DOI: 10.1002/csc2.20301
|View full text |Cite
|
Sign up to set email alerts
|

Guiding fall fertilization of cool‐season turfgrass lawns with NDVI sufficiency index

Abstract: Fall N fertilizers are applied to turfgrass at predetermined rates instead of being based on plant-N status. Normalized difference vegetative index (NDVI) and the sufficiency index (SI) concept are used to assess plant-N status in some agronomic crops but has not been evaluated for turfgrass. This study was conducted across 3 yr in Connecticut to determine fall and spring NDVI SI values in a mixed species, cool-season lawn. Field experiments were set out with varying fall N rates with NDVI measured weekly in O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Vegetation indices such as NDRE and NDVI have been evaluated as methods to guide N fertilization or quantify turfgrass response to fertilization (Kruse et al, 2006 ; Bremer et al, 2011a ; Lee et al, 2011 ; López-Bellido et al, 2012 ; Inguagiato and Guillard, 2016 ; Guillard et al, 2021 ). Our study demonstrated that there was a weak correlation between creeping bentgrass clipping yield and NDRE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vegetation indices such as NDRE and NDVI have been evaluated as methods to guide N fertilization or quantify turfgrass response to fertilization (Kruse et al, 2006 ; Bremer et al, 2011a ; Lee et al, 2011 ; López-Bellido et al, 2012 ; Inguagiato and Guillard, 2016 ; Guillard et al, 2021 ). Our study demonstrated that there was a weak correlation between creeping bentgrass clipping yield and NDRE.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we observed a weak positive correlation between daily clipping yield and NDRE when the N rate was based on the PACE Turf GP model (relatively higher N), whereas the correlation became negative once the N application rates were lower (experience-based, ML-RF model, and NDRE-based methods). Studies have concluded that NDRE has much stronger correlations with some turfgrass growth characteristics such as turfgrass biomass (Marín et al, 2020 ) and turfgrass N status (Guillard et al, 2021 ). These studies applied a wider range of N rates which resulted in large variation in turfgrass growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…New research should develop models and decision support systems to determine correct product and application rates for desired function and aesthetic goals similar to how precision agriculture research has focused on developing models and tools for farmers. Guillard et al (2021) developed fall-applied prescription N application models for lawn-height turfgrass in the Northeast United States, providing a PTM method for lawncare providers and homeowners to apply N more precisely to meet the turfgrass N needs. Straw et al (2020) developed a method to create SSMUs from time domain reflectometry soil volumetric water content data.…”
Section: Gaps Toward Adoption Of Precision Turfgrass Managementmentioning
confidence: 99%
“…Deployment of multispectral radiometry by researchers to characterize turfgrass canopy color, density, nitrogen (N) status, and/or a/biotic stress is increasing (Caturegli et al, 2020;Guillard et al, 2016Guillard et al, , 2020Pruyne et al, 2019Pruyne et al, , 2020Zhu et al, 2016). Justifications for adoption include rapid and repeatable measures of canopy reflectance by any number of operators.…”
Section: Introductionmentioning
confidence: 99%